1998
DOI: 10.1518/001872098779649265
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Communication Sequences for Team Training Needs Assessment

Abstract: Several models of team performance have suggested that a clearer understanding of team process is needed to determine better training formats and reduce crew-generated errors. The present study investigated the degree to which analyzing communication sequences would contribute to the understanding of effective crew process in two simulated flight tasks. The results indicate that pattern analyses reveal additional strong differences between performance groups that would have been overlooked by simple frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
4
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(133 citation statements)
references
References 6 publications
(6 reference statements)
4
121
4
1
Order By: Relevance
“…These findings suggest that a close relation exists between interactive group processes and effective threat and error management on the flight deck. A number of recent research studies have begun to explore the role of communication in error management and have focused on the identification of effective communication strategies (Bowers, Jentsch, Salas, & Braun, 1998;Fischer & Orasanu, 1999). However, the results of this study suggest that it is unlikely that any single communication strategy will be found to be most effective in relation to threat and error management, and stress that effective threat and error management involves Note.…”
Section: Predictors Of Threat and Error Managementmentioning
confidence: 99%
“…These findings suggest that a close relation exists between interactive group processes and effective threat and error management on the flight deck. A number of recent research studies have begun to explore the role of communication in error management and have focused on the identification of effective communication strategies (Bowers, Jentsch, Salas, & Braun, 1998;Fischer & Orasanu, 1999). However, the results of this study suggest that it is unlikely that any single communication strategy will be found to be most effective in relation to threat and error management, and stress that effective threat and error management involves Note.…”
Section: Predictors Of Threat and Error Managementmentioning
confidence: 99%
“…Utilizing various analysis techniques, aircrew communications research has found that communication sequences differ between effective and ineffective¯ight crews (e.g., Bowers et al, 1998). Thus, information sharing and team communications research could be combined to better explain how team members develop accurate expectations of team behavior.…”
mentioning
confidence: 99%
“…Team effectiveness is often reflected by the degree in which team members engage in processes for sharing information (Bowers et al 1998), while being engaged within both verbal and non-verbal communication. Poor SA is often associated with 596…”
Section: The Role Of (Situational) Awareness and Information In Team mentioning
confidence: 99%